Simulation of the Electro-Superconducting System Based on the H Equation - Jun Zhang (Journal of Chemistry)
In order to reduce the levitation energy consumption and increase the levitation air gap, a simulation study of the electrochemistry superconducting magnetic levitation system based on the H equation is proposed. Through finite element simulation, the magnetic field distribution, current distribution, force, and other characteristics of the magnetic suspension system in the superconducting gravimeter are obtained; the relationship between the force of the superconducting ball in the magnetic field and the height of the suspension body and the current of the suspension coil is analyzed; and the penetration rate, the magnetic gradient, penetration depth, and maximum magnetic induction intensity of the superconducting spherical surface of the single-coil electrochemistry superconducting magnetic levitation system are obtained by simulation calculation. Simulation results show that, at 1 s, we start to use 0.2 s, 0.4 s, 0.6 s, and 0.8 s time, respectively, to pass current into the floating coil until it reaches 4.4 A. The magnetic gradient of the electrochemistry superconducting magnetic levitation system using a single coil is too large to meet the requirements of gravity measurement, the penetration depth is much smaller than the thickness of the superconducting sphere, and the maximum magnetic field on the surface of the superconducting sphere is much smaller than the critical magnetic field value of the superconducting material, and no loss will occur. The critical magnetic field value of the superconducting sphere is much smaller than that of the superconducting sphere. The critical magnetic field value of the material will not quench, which verifies that the H equation can simulate the superconducting magnetic levitation system well and has a high simulation accuracy and efficiency.